Effect of aflatoxin on haematology, gross and histopathology of internal organs in white pekin ducks and its amelioration by dietary incorporation of bentonite clay - PALLAVI PRIYADARSHANI DAS; R C PATRA; S K PANDA; RAJASRI SAHOO; G R JENA; DHIRENDRA KUMAR (Indian Journal of Animal Sciences, 2023)
The present experiment was carried out to examine the effect of aflatoxin exposure through experimentally contaminated feed (48 or 98 μg/kg of feed) on hematological parameters, and gross and histopathology of liver, kidneys, thymus, spleen and bursa of fabricious in ducks, and to assess the prophylactic efficacy of bentonite clay at three different dose levels (1, 2 or 3g/kg of feed) in protecting the birds from the toxic effects of aflatoxin. The experiment was carried out on 9 weeks old white pekin ducks for a period of six weeks. The experimental ducks (n=72) were randomly divided into six equal groups. Group 1 birds served as healthy controls and were continued with basal diet without addition of toxin or bentonite clay. The birds of Group 2 were provided with a diet containing 48 μg toxin/kg of feed. The diet of the grower ducks of Group 3 to 6 were added with 96 μg of toxin/kg of feed. The birds of Group 4, 5, and 6 were provided with aflatoxin-contaminated feed and the diet was supplemented with bentonite clay @ 1, 2 or 3g/kg of feed, respectively. The hematological parameters such as Hb, PCV, TLC and Differential Leukocyte Count were estimated at 4th and 6th week post exposure. Haemoglobin, PCV and TLC reduced significantly in ducks fed with aflatoxin-contaminated feed. The birds fed with 48 μg aflatoxin/kg of feed had moderate gross lesions in different internal organs. The feed supplementation with bentonite clay in aflatoxin-exposed birds reduced the inflammation of hepatocytes.